2014
DOI: 10.1039/c4fo00113c
|View full text |Cite
|
Sign up to set email alerts
|

Study on chemical, bioactive and food preserving properties ofLaetiporus sulphureus(Bull.: Fr.) Murr.

Abstract: Laetiporus sulphureus (Bull.: Fr.) Murr. was studied to determine the nutritional value, bioactive compounds, in vitro antioxidants, and antimicrobial and antitumor activities. The studied mushroom is a rich source of carbohydrates and proteins. Mannitol and trehalose were the main free sugars. In addition, the polyunsaturated fatty acids a-, g-and d-tocopherols were found. Oxalic and citric acids were the most abundant organic acids; cinnamic and p-hydroxybenzoic acids were quantified in the methanolic extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 37 publications
(48 reference statements)
3
67
0
1
Order By: Relevance
“…Chromatogram identified trehalose as the dominant sugar (4 g/100 g DW), closely followed by mannitol (3.54 g/100 g DW), while fructose was present in minor amount (0.46 g/100 g DW). 4 …”
Section: Carbohydratementioning
confidence: 99%
See 3 more Smart Citations
“…Chromatogram identified trehalose as the dominant sugar (4 g/100 g DW), closely followed by mannitol (3.54 g/100 g DW), while fructose was present in minor amount (0.46 g/100 g DW). 4 …”
Section: Carbohydratementioning
confidence: 99%
“…The composition resulted in enrichment of PUFAs (64.14%) while saturated and monounsaturated fatty acids were present in lower amounts (20.54% and 15.32%, respectively). 4 Likewise, the lipid composition of two strains have demonstrated that overall mushrooms contain 80-90% water and 10-20% dry matter. 14,18 However, the water content in L. sulphureus has been reported to be lesser in quantity as it ranges from 72.69% to 66.67% (Table 1).…”
Section: Fatmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 Nowadays, mushroom research is intense and hundreds of species have demonstrated a broad spectrum of activities, including antimicrobial and antioxidant. 47 It is evident that there are very good effects of extracts, but there is a gap in the identification of the individual compounds responsible for antimicrobial properties. Only a few low-molecular weight compounds and some peptides and proteins have been described.…”
Section: Chemical Compositionmentioning
confidence: 99%